Domestic sexual violation: A legal commentary on spousal rape - Mohamad Yunus, Mohamad Ismail; Mohamad Hanifa, Shamshina (Universiti Tun Hussein Onn - UTHM, 2018)
Marriage is an institution, which casts upon a husband an obligation to respect a wife’s personal integrity and dignity; it does not give the husband a power to violate her personal integrity and destroy her dignity. It would be impossible to preserve, much less to foster, the institution of marriage as an exclusive union of man and wife for life if it were otherwise. To acknowledge a connubial obligation not to refuse sexual intercourse willfully and persistently is an acknowledgement that the giving of consent to acts of sexual intercourse is necessary to perform the obligation. It would have been inconsistent with such an obligation to hold that, on marriage, a wife’s general consent to acts of sexual intercourse has been given once and for all. If no further consent was required on the part of a wife, how could there be a wilful and persistent refusal of sexual intercourse by her? The Ecclesiastical Courts never embraced the notion of a general consent to sexual intercourse given once and for all on marriage by either spouse. The doctrine of the Ecclesiastical Courts was quite different, namely, that each spouse has a mutual right to sexual intercourse provided the right be exercised reasonably, subject to the health of the spouse and the exigencies of family life. It is a right to be exercised by consent. It is a right the exercise of which is intended to foster and maintain connubial love, not to be an occasion of abuse and degradation. It is noted that marital rape has its impact on wives physically and emotionally, thus justifying some legal jurists opinion to criminalize marital rape to protect these women. This impact is real and is not just to emotionalize the issue. Thus the book focuses on the issues of complicated process on obtaining protection order as the victims have to go through a certain period of time before the court grant them the protection. The second issue is on improving the enforcement of the law, even though the authorities keep improving their services and investigation, they should give priority to protect the victim from being abuse repeatedly. Lastly, lack of commitment or support from the community. The custom and culture avoid interference on other family problem had caused the victims to keep silent with their own. Without the community support the protection may not effectively achieve. This book studies comparatively on the legal positions under the common law jurisdictions, Malaysian law and Islamic law respectively.